Windstorm restoration efficiency using the Kidričevo windstorm (29 June, 2006) as a case study - Paulinič, Goran (Zbornik gozdarstva in lesarstva, 2008)
Economic efficiency is one of the many essential demands regarding the technical management of windstorms. The main goal of this paper is to analyze a hypothetical scenario in which a forest owner works independently on windstorm restoration, using his own equipment and work power. Managing windstorm damage is a difficult and dangerous task, although a potentially lucrative endeavour as our investigation shows. A windstorm represents an opportunity for instant profit for forest owners who are independent of regular forest income. Economic damage is greater and longer lasting for owners with large forest properties and for farm households, which depend on regular forest income. We compared two potential scenarios in a wind-damaged area within the 2000-2010 forestry management period. First, we include a hypothetical scenario in which the windstorm did not occur. An inventory of regular thinning as well as simulation of future events based on past dynamics was done. We also performed a second scenario in which we assumed that private owners carry out windstorm restoration alone, although in reality felling has been carried out with short-wood technology (mechanized cutting). The results section presents the possibilities to attain reasonably high yield by dealing with the consequences of a minor windstorm.
Keywords: gozdovi; sanacija; stroški; ujme; vetrolomi